Compressive behavior of liquid phase sintered 90 W-7Ni-3Fe heavy alloy at high temperature and low strain rate condition. (November 2018) - Yu, Yang; Ren, Chaoyuan; Zhang, Wencong
Abstract: The compressive behavior of 90 W-7Ni-3Fe heavy alloy prepared by liquid phase sintering is investigated systematically at strain rates 0.001, 0.01 and 0.1 s −1 and temperatures 298, 1073, 1273 and 1473 K. Compressive yield strength of the material increases with the increase of strain rate and decreases with the increase of temperature. The compressive deformation is affected by the coupling of work hardening and thermal softening; plastic deformation is dominated by work hardening at 298, 1073 and 1473 K below strain 0.5; plastic deformation is dominated by work hardening at 1473 K below strain 0.2. The work hardening rate decreases with the increase of strain and then tends to a relatively stable level. Microstructure evolution is sensitive to temperature and strain rate. The mechanical properties of specimen deteriorated significantly and the abnormal growth of W particles occurs at low strain rate (0.001 s −1 ) and high temperature (1473 K). The shear band with angle of about 45° to the compression direction appeared at the corner of samples at 1073 K. A large number of defects on phase interface appeared due to inconsistent deformation. Highlights: Compressive behavior of 90 W alloy at high temperature and low strain rate is discussed. The compressive behavior of 90 W alloys is affected by temperature, strain and strain rate. Obvious defects appear on microstructures and lead to decline in mechanical properties above 1473 K.